51.8k views
16 votes
The formula for any geometric sequence is an = a1 · rn - 1, where an represents the value of the nth term, a1 represents the value of the first term, r represents the common ratio, and n represents the term number. What is the formula for the sequence 2, -6, 18, -54, ...?

an = 2 · 3 n - 1
an = 2 · (-3) n - 1
an = -3 · 2 n - 1
an = 3 · 2 n - 1

User Nellute
by
4.7k points

1 Answer

12 votes

Answer:

The formula for the sequence is:
a_n = 2*(-3)^(n-1)

Explanation:

The general term of a geometric sequence is given by:


a_n = a_1*r^(n-1)

In which
a_1 is the first term and r is the common ratio between the terms, that is, the division between them.

What is the formula for the sequence 2, -6, 18, -54, ...?

First term is 2, so
a_1 = 2

Common ratio is given by:


r = (-6)/(2) = (18)/(-6) = ... = -3

So the sequence is given by:


a_n = 2*(-3)^(n-1)

User Elserj
by
4.3k points